Pola Komunikasi Organisasi Human Resource Development dalam Meningkatkan Motivasi Kerja Karyawan Generasi Y: Studi Kasus PT Eds Manufacturing Indonesia Automotive Wire - Nanda Abbrila Sastia; Aulian Khairani; Mochammad Mirza (Ikatan Da'i Indonesia, 2025)
This study aims to examine HR communication patterns in increasing work motivation among Generation Y employees at PT Eds Manufacturing Indonesia Automotive Wire and the obstacles HR faces in this effort. The research method used was qualitative, with data collected through observation, interviews with HR and several Generation Y employees, and documentation. Generation Y employees exhibit high absenteeism and low motivation, which impacts company productivity. Characteristics of this generation, such as the need for work-life balance and open communication, must be addressed. Despite the existence of reward and training programs, HR's role in fostering effective two-way communication remains crucial to increasing employee motivation, loyalty, and productivity.